2001
DOI: 10.1200/jco.2001.19.15.3483
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Clinical Investigation of Gemcitabine in Advanced Soft Tissue Sarcomas and Window Evaluation of Dose Rate on Gemcitabine Triphosphate Accumulation

Abstract: Given the limited therapeutic armamentarium for STS, the activity of gemcitabine is encouraging. Its potential for combination therapy in the salvage setting should be studied with pharmacologically guided fixed dose-rate infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
141
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(148 citation statements)
references
References 11 publications
4
141
1
2
Order By: Relevance
“…Thus, it was logical to examine a fixed-dose rate of gemcitabine in patients with sarcomas. The pharmacodynamics of gemcitabine in patients with sarcoma were consistent with those found in the pancreatic cancer study [20].…”
Section: Gemcitabinesupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, it was logical to examine a fixed-dose rate of gemcitabine in patients with sarcomas. The pharmacodynamics of gemcitabine in patients with sarcoma were consistent with those found in the pancreatic cancer study [20].…”
Section: Gemcitabinesupporting
confidence: 71%
“…These have generally involved gemcitabine with the U.S. Food and Drug Administration-approved bolus schedule, and have shown only low response rates [20,[22][23][24][25][26][27][28][29][30][31] (Table 1). Collectively, it is clear that uterine leiomyosarcoma is more sensitive to gemcitabine than other histologies and even leiomyosarcomas from other sites, and that other histologies can occasionally respond as well.…”
Section: Gemcitabine In Sarcoma Patients: Clinical Observationsmentioning
confidence: 99%
“…A study by Touroutoglou and colleagues showed that FDR gemcitabine (1,200 -2,800 mg/m 2 ) was safe and well tolerated [61]. Once-weekly administration of gemcitabine for 7 weeks of an 8-week cycle and FDR dosing of 1,000 mg/m 2 in 150 minutes demonstrated that intracellular levels of dFdCTP in peripheral blood mononuclear cells (PBMCs) increased linearly with infusion duration [69]. The maximum concentration (C max ) of dFdCTP was 1.4-fold higher after FDR than after standard gemcitabine.…”
Section: Phase I/ii Dose-finding Studies Investigating Prolonged (Fdrmentioning
confidence: 99%
“…Until recently, the differentiation between these two entities had not been thought to be clinically relevant. Chemotherapeutic agents, such as doxorubicin and ifosfamide used in the treatment of soft-tissue sarcomas have resulted in response rates of 0-10% in patients with advanced GIST (3)(4)(5). However, the use of the selective tyrosine kinase inhibitor imatinib mesylate [also known as STI571 (Gleevec; Novartis Pharmaceuticals Corp., East Hanover, NJ)] has resulted in response rates of Ͼ50% for patients with GIST (6, 7, **).…”
mentioning
confidence: 99%